Enhancing Critical Thinking Skills in Graduates: An Experiential Learning Approach - Hermita, Neni; Shirazi, Shaista; Talib, Corrienna Abdul; Ahmad, Nur Jahan (Jurnal Ilmiah Peuradeun, 2025)
Critical thinking is a vital 21st-century graduate attribute that significantly enhances employability and adaptability. This study investigated the effectiveness of experiential learning in fostering students’ critical thinking skills within the context of Indonesian higher education. Using a quantitative pretest-posttest design, data were collected from 117 university students enrolled in a science course at Universitas Riau. A structured questionnaire assessing five levels of critical thinking was used to measure students’ skills before and after the intervention. The findings revealed a statistically significant improvement in students’ critical thinking after the intervention (p < .001), with an average increase of 6.78 points and a 13.9% gain. Cohen’s d value of 0.84 indicated a large effect size. Post-intervention results showed a substantial shift in the distribution of critical thinking levels, with more students reaching the ‘superior’ and ‘exceptional’ categories. These results underscored the value of active, reflective, and real-world learning experiences in enhancing students’ cognitive skills. This study contributes to the growing body of evidence on pedagogical innovations in science education and offers practical implications for curriculum reform in developing countries.